Preliminary establishment of genetic transformation system for embryogenic callus of Acer truncatum ‘Lihong’ - Yang, Yipeng; Chan, Yuan; Wang, Yongge; Guo, Hao; Song, Lina; Zhang, Huali; Sun, Liping; Cong, Richen; Zhang, Hua (Frontiers in Plant Science, 2024)
In this study, leaves from five color-changing periods in autumn of ordinary Acer truncatum Bunge (CK) and Acer truncatum 'Lihong' (LH) were used as experimental materials. Through the analysis of transcriptome data, 110,872 unigenes were obtained after assembling the clean reads. By screening the differential genes in the five colorchanging periods of CK and LH varieties, a total of 11,984 DEGs were identified, among which 125 differential genes were shared across all five periods. By comparing the differences in expression levels in the transcriptome data, 59 genes related to anthocyanin synthesis were selected, with significantly higher expression levels in LH compared to the control. Among these, the GST genes were the most abundant, with 16 genes, generally showing higher expression in CK1, CK2, LH1, and LH2, and significantly higher expression in LH compared to CK. Through qRT-PCR experiments to verify gene expression, the gene GST894 was finally selected. Using the stems of Acer truncatum 'Lihong' as materials, a regeneration system for Acer truncatum 'Lihong' was established. A genetic transformation system for Acer truncatum 'Lihong' was established by Agrobacterium-mediated transformation of embryogenic calli of Acer truncatum 'Lihong'.The results showed that the best medium for callus induction of Acer truncatum was 1/2MS+2 mg/L 2,4-D+0.3 mg/L 6-BA+0.5 mg/L NAA; The embryogenic callus induction medium of Acer truncatum was 1/2MS+3.0mg/L 6-BA+2.0mg/L TDZ+0.5mg/L IBA+0.1mg/L GA3; The proliferation medium of embryogenic callus of Acer truncatum was WPM+1.0mg/L TDZ+0.5mg/L IBA+0.1mg/L GA3+3mg/L 6-BA+1.0mg/L KT; The 2 infection experiment of Agrobacterium tumefaciens on the embryogenic callus of Acer truncatum showed that the best antibacterial medium was WPM+30g/L sucrose+8g/L agar+0.5g/L acid-hydrolyzed casein+0.2mg/L KT+1.